Synthesis of alkyl- and poly(ethylene)glycol linked bis-dioxocyclams from bis-chromium carbene complexes - Kuester, Erik M., author; Hegedus, L. S., advisor (Colorado State University. Libraries, 2000)
Alkyl-linked bis-chromium carbene complexes have been prepared via deprotonation and α-alkylation of (methoxy)(methyl) chromium carbene complexes using l,n-bis-triflates as electrophiles. These bis-carbene complexes were then photolyzed with N-protected imidazolines to give protected bis-azapenams. Azapenams are known to undergo a dimerization reaction to form 14-membered bis-imine bis-dioxocyclams. Unfortunately, all attempts to reduce the imine-cyclams to give the stable dioxocyclams were unsuccessful. Both tri- and tetra(ethylene glycol) linked bis-chromium carbene complexes have been synthesized. These carbene complexes were photolyzed with imidazolines to give protected azapenams. The azapenams were transformed into polyether-linked basket dioxocyclams and bis-dioxocyclams. These compounds have cavities for the complexation of both "hard" and "soft" metal ions. The complexes of nickel, barium, and gadolinium were synthesized.
Keywords: organic chemistry